(untitled) (Journal of Engineering, 2014)
This study investigates the performance of granular dead anaerobic sludge (GDAS) bio-sorbent as permeable reactive barrier in removing phenol from a simulated contaminated shallow groundwater. Batch tests have been performed to characterize the equilibrium sorption properties of the GDAS and sandy soil in phenol-containing aqueous solutions. The results of GDAS tests proved that the best values of operating parameters, which achieve the maximum removal efficiency of phenol (=85%), at equilibrium contact time (=3 hr), initial pH of the solution (=5), initial phenol concentration (=50 mg/l), GDAS dosage (=0.5 g/100 ml), and agitation speed (=250 rpm). Fourier transform infrared (FTIR) analysis proved that the carboxylic acid, aromatic, alkane, alcohol, and alkyl halides groups are responsible for the bio-sorption of phenol onto GDAS. A 2D advection-dispersion, solved numerically by computer solutions (COMSOL) Multiphysics 3.5a software which is based on the finite element method, has been used to simulate the equilibrium transport of phenol within groundwater. This model is taking into account the pollutant sorption onto the GDAS and sandy soil which is represented by Langmuir equation. Numerical and experimental results proved that the barrier plays a potential role in the restriction of the contaminant plume migration. Also, the barrier starts to saturate with contaminant as a function of the travel time. A good agreement between the predicted and experimental results was recognized with root mean squared error not exceeded the 0.055.